BIOGEOCHEMICAL CHARACTERISTICS OF THE ELEMENT ZINC (Zn) IN GRAY-BROWN AND ONION (Allium cepa L.) - Isomiddinov Zakirjon Jaloldinovich; Mamurov Khurshidjon Abduvokhidovich,Ghulomjanov Mirzadavlatbek Daniyorjan ogli; Shalabaev Karatay Isqaguly (Galaxy International Interdisciplinary Research Journal, 2022)
The article analyzes the biogeochemical characteristics of zinc (Zn) content of onion (Allium cepa L.) in the layer of irrigated gray-brown soils distributed in Fergana region, and the importance of zinc (Zn) content in the soil for the growth and development of onion plants in the cultivation of onion crops. proven.